(untitled) (Training and Practice : Journal of Educational Sciences, 2012)
This study was born with the aim of introducing and putting further emphasis on the role, function and purpose of lnformation Communication Technology in education. Information Communication Technology offers complex learning facilities, which as up-to-date and effective tools can support the learning-teaching process in an excellent way therefore their extensive application is indispensable. Nowdays schools can function properly and meet the requirements of the information age, if they provide their students with a wide range of learning supporting facilities, which are used to create equal opportunities for them to acquire knowledge. Therefore all educational establishments such as the Benedictine Secondary Grammar Schools, which have great histories and which gave birth to education in Hungary, strive to apply modern technologies in their teaching and educational work, which will be covered in this study.